Men in a developing society : geographic and social mobility in Monterrey, Mexico - Balán, Jorge, 1940-; Browning, Harley L.; Jelin, Elizabeth, 1941- (Latin American monographs (University of Texas at Austin. Institute of Latin American Studies), 1973)
Case study of social mobility and labour mobility in Mexico, based on an interview survey of 1640 men (including migrant workers) in the monterrey urban area and 380 rural migration-prone men in a nearby rural community - examines the consequences of economic development for individual workers as revealed in their life histories, covers adaptability, social change, etc., and includes the research methodology. Bibliography pp. 359 to 373, diagrams, references and statistical tables.